Successful Use of Endoscopy for Transcervical Cannulation Procedures in the Goat. Issue 6 (15th September 2014) - Colagross‐Schouten, A; Allison, D; Brent, L; Lissner, E
Contents Two methods for transcervical cannulation of the goat were evaluated during a contraception study in 15 adult female Nigerian dwarf and African pygmy goats. Twenty‐four transcervical cannulation procedures were conducted in which seven females underwent the procedure 2–3 times. Initially, a rigid 4‐mm stainless steel cannula and external light source were used in 19 procedures to introduce the contraceptive compound into the uterus. Placement of the cannula was directed by feel or depth assessment. Of seven females that were euthanized following this procedure, four evidenced complications including penetration of the cervix with the cannula and cervical damage. A 2‐mm custom‐made endoscope with a specially designed cannula was then used for the remaining five procedures. No complications were found. A single animal, that underwent the endoscopic procedure twice, was euthanized for study purposes and no abnormal findings of the reproductive tract were reported. The use of an endoscope resulted in better outcomes because the uterus could be visualized after traversing the cervix.